Influence of fatigue and acute caffeine supplementation in badminton men`s singles - Chia, J. (2018)
The game of badminton is increasing not only in popularity but also in its pace and intensity. With an intense and dynamic activity profile, it is not surprising that fatigue influences performance. While there have been notational analyses performed for badminton singles match play, the literature on both cognitive and physical fatigue and its influence on performance is limited owing to the inherent difficulty in inducing fatigue in a controlled experimental setting. Moreover, apart from observable match variables and physiological responses, changes to underlying perceptual processes such as aiming are harder to identify. Yet, these changes provide key information to both athletes and coaches when designing training interventions to minimize the decrement(s) in performance associated with fatigue. The aims of this thesis were twofold. Firstly, to develop a badminton-specific protocol to investigate the influence of fatigue on singles match performance, serve accuracy and visual behaviour. Secondly, to evaluate the effect of caffeine on serve performance and exercise capacity. To achieve these aims, one pilot study and three main studies were conducted. To investigate the changes in visual behaviour during serving, the feasibility of the use of a mobile eye tracker was first evaluated in a pilot study. Thereafter, a novel badminton specific protocol involving the use of a shuttle launcher was designed (Chapter 4). The protocol elicited similar physiological responses as actual match play and had excellent test-retest reliability for all performance and objective markers of physiological stress. This protocol was used to induce fatigue and the changes in match behaviour during a 25 min simulated match, and serve accuracy was explored (Chapter 5). Though there was no significant impact on direct point(s) won/loss with fatigue, changes in shot selection were observed with players using more smash shots following fatigue (22.8 % vs. 17.8 %), p = 0.047. Long serve accuracy decreased with fatigue (radial error: 141.6 cm to 155.5 cm) without any changes in visual strategy. There was also no clear relationship between serve performance and quiet eye - the final aiming point and duration. To counter the effects of fatigue and enhance performance, approximately 74 % of elite athletes, in general, consume caffeine. In the final study, the effect of an acute dose of 6.0 mg·kg-1 BM of caffeine on exercise capacity and serve performance was investigated in elite male badminton players (Chapter 6). Time to exhaustion on the badminton protocol was longer for 75 % of the participants (8.9 % to 184.8 % improvement). Serve accuracy, however, was unaffected both positively and negatively by caffeine. No major side effect(s) were reported; this dosage is thus considered to be a safe ergogenic aid. Key contributions from this thesis include the successful development of a badminton- specific protocol which induces match-like fatigue and a more in-depth understanding of fatigue on badminton performance. While there were no changes in visual behaviour with fatigue, long serve accuracy decreased, suggesting other possible limiting factors such as muscular fatigue. Insights to the choice of shot types in the fresh and fatigued state were also drawn from this thesis. Finally, caffeine might be beneficial in helping elite players to last longer in an actual match. However, considering the individual variation in responses, caffeine ingestion strategies should be implemented on a case- by-case basis.